Rancang Bangun Sensor Jarak sebagai Alat Bantu Memarkir Mobil berbasis Mikrokontroler Arduino Uno - Henriques, Pedro Paulo De J. Costa; Agung, I. G. A. P Raka; Jasa, Lie (Jurnal Teknologi Elektro; Vol 17 No 1 (2018): (Januari - April) Majalah Ilmiah Teknologi Elektro, 2018)
Abstract — Cars are a transportation mode that is widely used in society. Every year in Indonesia and other countries experience a continuous increase in the number of cars. The intensity of cars especially in parking areas often become a challenge for drivers to park cars and increases the risk of a crash. This research aims to design and build a distance sensor device that helps to park cars based on Arduino Uno microcontroller which is hoped to help decrease the risk of cars crashing to another car or object. This device will will produce three types of input that will inform the driver on the distance detected, between the car and another object. The first output is in text form displayed on an LCD screen, then the second output is a buzz produced by a buzzer and the third output is produced by a speaker which produces sound of audio recordings voicing the distance detected by the sensor.